Bibliographic survey of the mechanism of development of Type II Diabetes Mellitus after infection by SARS-COV-2 (Research, Society and Development, 2022)
This study aims to conduct a systematic review of the literature to understand the mechanism of development of type II DM after SARS-COV-2 infection and to point out new updates on the subject. Currently, the world faces the pandemic of Coronavirus Disease 2019, a severe acute respiratory syndrome caused by coronavirus SARS-COV-2, having as one of the most frequent pathological consequences diabetes mellitus type II (Type II DM). DM type II is a metabolic endocrine dysfunction characterized by excess circulating glucose in the blood due to defects in the secretion and/or action of insulin, thus hindering the use of glucose as an energy source for the homeostatic metabolic functions of the human body. To date, several epidemiological studies indicate that a high pathological relationship between Covid-19 and DM type II where both pathologies complement each other to generate simultaneous harmful damage. By bringing pancreatic beta cell dysfunction, SARS-COV-2 can induce transient acute hyperglycemia or lead to a genetically predisposed individual developing DM type II. The prevalence of DM type II in patients recovering from post-covid 19 infection is notorious, but new searches to better understand its etiology are crucial.